PERTANGGUNGJAWABAN NOTARIS TERHADAP AKTA HIBAH SAHAM YANG TIDAK SESUAI PROSEDUR RUPS (STUDI KASUS PUTUSAN NOMOR 10/PDT.G.S/2023/PN Pdg) - Alkadrie, Syarif Muhammad Billy Notosatrio (Faculty Of Law, Universitas Tanjungpura, 2025)
Abtsract This study aims to know, analyze, and examine 2 (two) things, first, the regulation of the responsibility of Notaries who are not careful in making Stock Grant Deeds that are not in accordance with RUPS procedures based on Decision Number 10/PDT. G.S/2023/PN Pdg. Second, the legal sanction of the Notary for losses arising from his carelessness in making the Share Grant Deed that is not in accordance with the procedure and causes losses based on Decision Number 10/PDT. G.S/2023/PN Pdg. The method used is a normative legal research method which is carried out by researching literature materials, using a statute approach The approach used in this study is a legal approach, a concept approach, and a case study approach. Data collection techniques with literature studies. The data analysis technique used in this study is legal interpretation. Based on the results of the research and discussion, a conclusion was obtained. First, the arrangement of accountability for Notary Haryanti S.H requires the form of responsibility that can be given, namely the form of administrative responsibility. The provision of administrative responsibility is in the form of a reprimand or warning, which is carried out orally or in writing by the Regional Supervisory Council of the Indonesian Notary Association. Second, the legal sanctions that can be given to Notary Haryanti S.H are administrative sanctions. Notary Haryanti S.H cannot be sued civilly on the basis of committing an unlawful act (onrechtmatige daad) as stipulated in Article 1365 of the Civil Code because Notary Haryanti S.H has met the requirements for formal truth. In terms of criminal sanctions, Notary Haryanti S.H does not meet the aspects as a Notary who commits a criminal act. The imposition of criminal sanctions against Notary Haryanti S.H cannot be carried out. Abstrak Penelitian ini bertujuan untuk mengetahui, menganalisis, serta mengkaji 2 (dua) hal, pertama, pengaturan mengenai tanggung jawab Notaris yang tidak hati - hati dalam membuat Akta Hibah Saham yang tidak sesuai prosedur RUPS berdasarkan Putusan Nomor 10/PDT.G.S/2023/PN Pdg. Kedua, sanksi hukum Notaris atas kerugian yang timbul akibat ketidak hati - hatiannya membuat Akta Hibah Saham yang tidak sesuai prosedur dan menyebabkan kerugian berdasarkan Putusan Nomor 10/PDT.G.S/2023/PN Pdg. Metode yang digunakan adalah metode penelitian hukum normatif yang dilakukan dengan cara meneliti bahan pustaka, dengan menggunakan pendekatan perundang - undangan (statute approach). Pendekatan yang digunakan dalam penelitian ini adalah pendekatan undang